The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7759/cureus.11289
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in Saudi Children: Presentation, Complications, and Treatment Outcome

Abstract: Background Brucellosis, an endemic disease in Saudi Arabia, has an infection rate of 70 per 100,000 people, with a varying morbidity rate in different parts of the country. The aim of this study was to assess the epidemiological and clinical features, laboratory findings, treatment modalities, complications, and outcomes in children with brucellosis. Materials and methods The medical records of 153 patients attending King Abdullah Specialist Children’s Hospital in Riyadh, Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Brucellosis is an endemic zoonotic disease in most countries of the MENA region. For example, in Saudi Arabi, the incidence of brucellosis is estimated to be 70 per 100,000 people/year [6] . Up to 30% of the reported cases are children [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis is an endemic zoonotic disease in most countries of the MENA region. For example, in Saudi Arabi, the incidence of brucellosis is estimated to be 70 per 100,000 people/year [6] . Up to 30% of the reported cases are children [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Qasim et al's study included 153 Saudi children with Brucella, 80% of them had fever and mild symptoms. 8 Moreover, Ghaly et al reported that 24% of children with Fever of Unknown Origin in Egypt are caused by brucellosis. Therefore, it is recommended that in the evaluation of patients transplanted with unknown fever, even if the symptoms do not imply brucellosis, we should think about this disease and perform the necessary tests.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Qasim et al obtained a positive blood culture in 34% of children with Brucella. 8 Since diagnosis is confirmed by obtaining the germ of the causative agent, it is necessary to perform blood culture in all patients and, if possible, bone marrow culture and keep the sample for a long time (at least 30 days) or use BACTEC medium, if appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Triple therapy with IV ceftriaxone, doxycycline, and rifampicin showed an excellent response and clinical improvement. The presented case was part of a retrospective cohort study that aimed to describe the clinical presentations and treatment strategies of brucellosis among Saudi children [ 8 ].…”
Section: Discussionmentioning
confidence: 99%